The Trojan Player Typology: A cross-genre, cross-cultural, behaviorally validated scale of video game play motivations. (August 2015) - Kahn, Adam S.; Shen, Cuihua; Lu, Li; Ratan, Rabindra A.; Coary, Sean; Hou, Jinghui; Meng, Jingbo; Osborn, Joseph; Williams, Dmitri
Highlights: New scale developed for motivations to play video games. Validated using a North American MOBA and a Chinese MMO. Validated using both survey and server-side behavioral measures. Abstract: While many video game researchers have built scales to tackle the motivations that people have for playing video games, these scales are often limited by their focus on specific game genres or player cultures as well as their lack of behavioral validation. The present research offers a new scale for player motivations and then examines its validity across two distinct gaming genres and cultures, drawing from server-side data combined with survey data of 18, 627 players of the Multiplayer Online Battle Arena League of Legends and 18, 819 players of the Chinese Massively Multiplayer Online Game Chevalier's Romance Online 3 . Six types of player motivations were found: socializer, completionist, competitor, escapist, story-driven, and smarty-pants. Consistent with previous research on player motivations, this typology offers new insights into why people play video games and how player motivations can be used to infer players' in-game behaviors.